2019
DOI: 10.1029/2018gc008170
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Variable Slab Dip in Driving Mantle Flow at the Eastern Edge of the Alaskan Subduction Margin: Insights From Shear‐Wave Splitting

Abstract: Alaska provides an ideal tectonic setting for investigating the interaction between subduction and asthenospheric flow. Within the span of a few hundred kilometers along strike, the geometry of the subducting Pacific plate varies significantly and terminates in a sharp edge. Furthermore, the region documents a transition from subduction along the Aleutian Arc to strike‐slip faulting along the Pacific Northwest. To better understand mantle interactions within this subduction zone, we conduct an SKS shear‐wave s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 86 publications
(214 reference statements)
13
47
1
Order By: Relevance
“…Jadamec and Billen () favored the shorter, shallower slab model, which produced horizontal flow consistent with the shear wave splitting patterns shown in Christensen and Abers (), and toroidal flow around the inferred edge of the Pacific plate. The shear wave splitting results of Venereau et al () agree with this model to the east of the slab and are very similar to our results. Our new shear wave splitting results may support this interpretation, in that there appears to be a general circular pattern of fast directions centered between the inferred edges of both the Pacific and Wrangell slabs (pink symbols; Figure ), with many null measurements that may be indicative of vertical anisotropy (vertical flow) (Figure ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Jadamec and Billen () favored the shorter, shallower slab model, which produced horizontal flow consistent with the shear wave splitting patterns shown in Christensen and Abers (), and toroidal flow around the inferred edge of the Pacific plate. The shear wave splitting results of Venereau et al () agree with this model to the east of the slab and are very similar to our results. Our new shear wave splitting results may support this interpretation, in that there appears to be a general circular pattern of fast directions centered between the inferred edges of both the Pacific and Wrangell slabs (pink symbols; Figure ), with many null measurements that may be indicative of vertical anisotropy (vertical flow) (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…There are 2,389 results from 386 stations from this study plotted in pink in Figure , and the 842 results from Perttu et al () and Christensen and Abers () are shown in red in Figure . Venereau et al () used a subset of the stations that we do in our study region and find similar large‐scale splitting patterns across Alaska.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, as we suggested above, we attribute the trench‐parallel flow to the edge effect by the eastward subducted South China Sea Plate. It is possible that the flow is wrapping around the slab edge as suggested to occur in other subduction zones like in Alaska (e.g., Venereau et al, ) and Ryukyu (Kuo et al, ) but which needs more observations to draw a conclusion. The interpreted 2‐D corner flow and deflected flow due to edge effect in this area are both displayed schematically in Figure .…”
Section: Discussionmentioning
confidence: 96%
“…The anisotropy resulting from the 2‐D corner flow or the slab‐entrained flow often exhibits trench‐normal fast directions (more precisely, parallel to the APM of subducting slabs). However, due to the influences from a number of factors such as trench migration, proximity to slab edges, slab morphology, existence of slab window, local thermal anomaly, and volatile distribution, the resultant flow pattern and anisotropic parameters exhibit a large variations worldwide (see a more detailed review by Long, ); specifically, small‐scale flow and 3‐D toroidal flow have been found in subduction zones (e.g., Faccenna & Becker, ; Venereau et al, ), and trench‐parallel flow also exists below the subducting slabs (e.g., Russo & Silver, ). In addition, slab‐slab interaction between two neighboring subducting plates (e.g., Király et al, ) also likely plays a role in complicating the flow fields in subduction zones.…”
Section: Seismic Anisotropy In Subduction Zonesmentioning
confidence: 99%